New Entropies, Black Holes, And Holographic Dark Energy - Nojiri, S.; Odintsov, S. D.; Faraoni, V. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
The Bekenstein-Hawking entropy is a cornerstone of horizon thermodynamics but quantum effects correct it, while inequivalent entropies arise also in non-extensive thermodynamics. Reviewing our previous work, we advocate for a new entropy construct that comprises recent and older proposals and satisfies four minimal key properties. The new proposal is then applied to black holes and to holographic dark energy and shown to have the potential to cause early universe inflation or to alleviate the current Hubble tension. We then analyze black hole temperatures and masses consistent with alternative entropies. Энтропия Бекенстейна-Хокинга является краеугольным камнем термодинамики черных дыр, но квантовые эффекты дают поправки к ней. Не эквивалентные энтропии появляются также в не-экстенсивной термодинамике. Мы делаем обзор предыдущих работ и предлагаем новую энтропию, которая обобщает другие варианты энтропий и удовлетворяет четырем ключевым условиям. Новая энтропия рассмотрена в теории черных дыр и голографической темной энергии. Показано, что она может объяснить инфляцию ранней Вселенной и указать на возможность решить недавнюю проблему с параметром Хаббла. Сделан также анализ температур и масс черных дыр совместимых с альтернативными энтропиями.
Keywords: Astrophysics